2008
DOI: 10.1007/s12031-007-9029-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive Steroid Levels in a Transgenic Rat Model of CMT1A Neuropathy

Abstract: Charcot-Marie-Tooth type 1A (CMT1A) represents 80% of all the demyelinating hereditary motor and sensory neuropathies. As recently suggested, neuroactive steroids may have a role in a therapeutic strategy for peripheral neuropathies, including CMT1A. To this aim, an accurate qualitative and quantitative analysis of neuroactive steroid levels in this disease could be extremely important to define effective pharmacological strategies. We here analyzed by liquid chromatography-tandem mass spectrometry the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…This is in agreement with the general decrease of neuroactive steroid levels observed in different animal models of neurodegeneration, such as Parkinson's disease, multiple sclerosis, peripheral neuropathies and diabetic encephalopathy [31,171,[183][184][185][186][187][188][189][190][191][192][193].…”
Section: Effects Of 5α-ri Therapy On Neurobehavioral Functions and Nesupporting
confidence: 84%
“…This is in agreement with the general decrease of neuroactive steroid levels observed in different animal models of neurodegeneration, such as Parkinson's disease, multiple sclerosis, peripheral neuropathies and diabetic encephalopathy [31,171,[183][184][185][186][187][188][189][190][191][192][193].…”
Section: Effects Of 5α-ri Therapy On Neurobehavioral Functions and Nesupporting
confidence: 84%
“…Investigating neuroactive steroid changes directly in the CNS, particularly under experimental conditions replicating specific neurological conditions, may be of vital importance to set the ground for specific therapeutic approaches based on these agents. We have recently applied the assessment of neuroactive steroids, by liquid chromatography tandem mass spectrometry (LC-MS/MS), in different experimental models of neurodegeneration, observing that their levels are affected by the neuronal pathology (Caruso et al 2008a;Caruso et al 2008b;Caruso et al 2010;Giatti et al 2010;Melcangi and Garcia-Segura 2010;Pesaresi et al 2010). However, scarce information has been so far obtained in PD.…”
Section: Introductionmentioning
confidence: 99%
“…As reported, women show higher disability than men [100], association of restless legs syndrome and polyneuropathy, as well as sensory neuropathy of small fiber type [101]. Data obtained in an experimental model of CMT1A have shown that the levels of isopregnanolone are decreased only in female sciatic nerve, while those of 3a-diol are decreased in only male [49].…”
Section: May Neuroactive Steroids Be the Basis Of Sex-oriented Treatmmentioning
confidence: 80%
“…Indeed, as demonstrated in experimental models and clinical studies, neurodegenerative and psychiatric disorders affect neuroactive steroid levels [13,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. For instance, neuroactive steroid levels are modified in experimental models of acquired peripheral neuropathy, such as those due to trauma [68] or diabetes [50,61] and inherited peripheral neuropathy (e.g., Charcot-Marie-Tooth type 1A, CMT1A) [49]. Pathological conditions also modified neuroactive steroid levels in CNS.…”
Section: Neural Pathology Influences Neuroactive Steroid Levelsmentioning
confidence: 99%